Determinar el rendimiento a la aplicación de tres niveles de fertilización con dos bioestimulantes enraizadores en el cultivo de pepino dulce (solanum muricatum aiton) en la zona de Ibarra, provincia de Imbabura - Andrango Vaca, Jesús Cornelio (2015)
This research on the response of the three-tier application of chemical fertilizer supplemented with bioestimulantes Rooting in the cultivation of sweet cucumber (PepinoAiton) in the area of Ibarra, was held in the agricultural sector of Barrio San Jose, parish of La Dolorosa , Canton Ibarra in Imbabura Province. Geographical coordinates are 00 ° 23 '33' 'north latitude, 78 ° 06' 31 '' west longitude, at an altitude of 2240 m This work was performed in order to evaluate the agronomic performance and crop yield fresh cucumber applying three levels of chemical fertilization and two Rooting bioestimulantes Ibarra area. Sweet variety "Aiton" cucumber was planted using cuttings. The treatments were seven conformed with the Radical bioestimulantes fit and Kelpak at doses of 2.5 ml / l and NPK fertilizer in doses of 25, 35 and 45 g / plant, with four replications. The design of a randomized complete block was used and for comparison of the average of the results of treatments Tukey test was used at 5% significance. During the growing season all the work required and agricultural practices such as chemical analysis of soil, fertilization, irrigation, weed control, pests and diseases were made. The variables measured were days to arrest, days to flowering, number of fruits per plant, fruit weight and equatorial diameter of the fruit........